Mini-Review: The importance of an integrated approach to assess trace mineral feeding practices in dairy cows - Duplessis, Mélissa; Royer, Isabelle (Frontiers in Animal Science, 2023)
This mini-review was undertaken to demonstrate the importance of considering the impact of trace mineral feeding management of dairy cows on the whole ecosystem by discussing their role in the animal metabolism, dietary recommendations, current feeding practices, and their excretion in manure pertaining to five trace minerals, i.e., cobalt, copper, iron, manganese, and zinc. The first part of this mini-review relates the importance of trace minerals in dairy cow metabolism, and how requirements are obtained. The following section showed that the transition period from the dry to the lactating phase is challenging for dairy cattle, and current trace mineral recommendations have been questioned for this period due to the role of some trace minerals in immunity and oxidative metabolism. Furthermore, trace mineral overfeeding is a common practice in intensive dairy production system in Canada, the USA, and the UK, which is far from precision nutrition. Trace minerals in excess of requirements are directly excreted into the manure. The practice of trace mineral overfeeding could have detrimental effects on the whole ecosystems when manure with high trace mineral concentrations is repeatedly spread on fields. In conclusion, an integrative approach assessing the impact of trace mineral overfeeding in cow diets on the whole ecosystems is needed.